Transportation asset management methodology and applications - Li, Zongzhi (CRC Press, 2020)
Transportation asset management delivers efficient and cost-effective investment decisions to support transportation infrastructure and system usage performance measured in economic, social, health, and environmental terms. It can be applied at national, state, and local levels. This is the first book to address asset management for multimodal transportation, taking account of system component interdependency, integration, and risk and uncertainty. It sets out rigorous quantitative and qualitative methods for addressing system goals, performance measures, and needs; data collection and management; performance modeling; project evaluation, selection, and trade-off analysis; innovative financing; and institutional issues. It applies as easily to static traffic and time-dependent or dynamic traffic which exists on a more local level. It is written for transportation planners, engineers, and academia, as well as a growing number of graduate students taking transportation asset management courses.